2013
DOI: 10.1039/c3sm51029h
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pH on the self-assembly of a collagen derived peptide amphiphile

Abstract: Transitions in nanostructure driven by pH are observed for a selfassembling peptide amphiphile (PA) with a cationic pentapeptide headgroup. At pH 3, the PA forms flat tape-like structures, while at pH 4 the PA assembles into twisted right handed structures. These twisted structures transform again to flat tape-like structures at pH 7. In complete contrast, spherical micelles are observed at pH 2. These changes in response to pH may be relevant to biological and pharmaceutical applications of this PA in skincar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 19 publications
(33 reference statements)
5
60
1
Order By: Relevance
“…31 As shown in Fig. 3b, the peptide motif KLVFF (Aβ [16][17][18][19][20] self-assembled into 2D membranes under the influence of hydrated electrons coming from argon glow discharge. Meanwhile, the metal ions in solution could be simultaneously reduced to MNPs (Au, Pt, Ag and Pd) by these high-energy electrons.…”
Section: Peptide and Noble Mnp Nanohybridsmentioning
confidence: 90%
See 2 more Smart Citations
“…31 As shown in Fig. 3b, the peptide motif KLVFF (Aβ [16][17][18][19][20] self-assembled into 2D membranes under the influence of hydrated electrons coming from argon glow discharge. Meanwhile, the metal ions in solution could be simultaneously reduced to MNPs (Au, Pt, Ag and Pd) by these high-energy electrons.…”
Section: Peptide and Noble Mnp Nanohybridsmentioning
confidence: 90%
“…18,34,95,96 For example, due to its effect on migrating and adhering endothelial cells, collagen-mimetic peptide containing sequence RGD is expected to mimicking extracellular matrix (ECM) for a long period of time. 34 In a metal-promoted assembly process, metal-ligand pairs could serve as anchors for the crosslinking of His-tagged biomolecules.…”
Section: Other Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference of Rms roughness was also significant (P < 0.05) at different pH values. It was demonstrated that the solution of pH values played an important role in influencing the adsorption of anions and cations at the solid-liquid interfaces during collagen selfassembly [21,22]. The molecular structure of collagen is the trimer-of-phase [ 1 (I)] 2 2 (I), which is composed of 1 (I) and 2 (I) chains.…”
Section: Effects Of Ph Values On the Collagen Self-assemblymentioning
confidence: 99%
“…The PA C 16 -KTTKS has been shown to have β-sheet secondary structure and form bilayer-based nanotapes 32 which are stable between the pH range of 3-7 at room temperature. However, pH reduction/increase 64 or increased temperature 65 favours random coil secondary structure, and spherical micelle self-assembly.…”
mentioning
confidence: 99%